Gambaran eGFR Menurut CKD-EPI pada Penderita Thalassemia Mayor di Rumah Sakit Dr. Hasan Sadikin Bandung - Doloksaribu, Rismauli; Husna, Rizka; Oehadian, Amaylia (Majalah Kedokteran Bandung, 2017)
Peningkatan harapan hidup penderita thalassemia menyebabkan manifestasi penyakit pada berbagai organ, termasuk ginjal. Estimated glomerular filtration rate (eGFR) adalah penghitungan untuk mendeteksi gangguan dini fungsi ginjal, cara ini lebih dipercaya dibandingkan nilai kreatinin serum. The National Kidney Foundation merekomendasikan Chronic Kidney Disease  Epidemiology Collaboration (CKD-EPI) untuk mengestimasi laju filtrasi glomerulus. Penelitian ini bertujuan mengetahui gambaran eGFR menurut CKD-EPI  pasien thalassemia. Penelitian menggunakan metode deskriptif. Data diambil dari penderita thalassemia mayor rawat jalan di Klinik  Hematologi Onkologi Medik, Rumah Dr. Sakit Hasan Sadikin Bandung, mulai 1 Februari sampai dengan 31 Maret 2016. Diperiksa kadar kreatinin serum dan penghitungan eGFR berdasar atas CKD-EPI. Dari 108 subjek penelitian, didapatkan usia rata-rata 18 tahun dengan jumlah wanita sebanyak 61,1 %. Gambaran eGFR berdasarkan CKD-EPI: menunjukkan hiperfiltrasi glomerulus pada mayoritas pasien dengan eGFR >120 mL/menit.  Pemeriksaan fungsi ginjal pasien thalassemia diperlukan untuk memantau gangguan fungsi ginjal dan untuk pemilihan penggunaan jenis kelasi besi. [MKB. 2016;49(1):22–7]Kata kunci: CKD–EPI, eGFR, thalassemia eGFR Profile Based on CKD-EPI of Thalassemia Mayor Patients in Dr. Hasan Sadikin General Hospital BandungIncreased life expectancy of thalassemia patients has a consequence of various manifestations of the diseases in many organs including kidney. Estimated glomerular filtration rate (eGFR) can be used for detecting early renal dysfunctions due to the fact that this calculation is more accurate compared to creatinine serum measurement. The National Kidney Foundation recommends Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) for estimating GFR. The aim of this descriptive study was to describe eGFR profile based on CKD-EPI in thalassemia patients. Data were collected from ambulatory patients visiting the Hematology Oncology Medical Clinic of Dr. Hasan Sadikin General Hospital during the period of February 1, 2016 to March 31, 2016. Subjects were patients with thalassemia major. Creatinine serum level  and calculated eGFR based on CKD-EPI were evakyated.  One hundred and eightsubjects with a median age of 18 years participated in this study with 61.1%  of them were female. According to the Kidney Disease Improving Global Outcomes  ( KDIGO) 2012, the eGFR calculation based on CKD-EPI showed that the majority of patients experience glomerular hyperfiltration (eGFR >120 ml/mnt). In this study, most Thalassemia major patients showed glomerular hyperfiltration. Renal function test is needed to monitor renal function abnormalities and to choose  the type of iron chelation therapy to be implemented. [MKB. 2016;49(1):22–7]Key words: CKD-EPI, eGFR, thalassemia